2021
DOI: 10.31590/ejosat.841922
|View full text |Cite
|
Sign up to set email alerts
|

Şebekeden Bağımsız Ev Tipi Uygulamaları için PCM Destekli PV/T Kollektörlerinin Deneysel Analizi

Abstract: An experimental study was carried out to examine the efficiency of solar energy in photovoltaic thermal collectors (PV/T) with energy storage. A photovoltaic thermal collector was used to generate both electrical energy and hot water. The effects of inclination angle of PV/T collectors on power, temperature, energy and exergy values were investigated. Also, effects of cellular shading are tested and discussed. PV/T was compared with the conventional PV/T collector by adding phase change material (PCM) for one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The power output increased by 7.4 W. Thermal efficiencies were 58.35% in the PV/T system, whereas 70.34% in the PCM integrated system, which indicated that the efficiency was increased by cooling the back of the panel. Bakır et al (2021) investigated the effect of different shading conditions on collector power and hot water output by comparing PV/T systems with and without PCM. Experiments were carried out in Turkey on days when the weather was not cloudy in July.…”
Section: Water Cooled Pv/t-pcm Systemsmentioning
confidence: 99%
“…The power output increased by 7.4 W. Thermal efficiencies were 58.35% in the PV/T system, whereas 70.34% in the PCM integrated system, which indicated that the efficiency was increased by cooling the back of the panel. Bakır et al (2021) investigated the effect of different shading conditions on collector power and hot water output by comparing PV/T systems with and without PCM. Experiments were carried out in Turkey on days when the weather was not cloudy in July.…”
Section: Water Cooled Pv/t-pcm Systemsmentioning
confidence: 99%